The Mediating role of identity status on parental involvement, and risk behaviors among Filipino emerging adults - Samala, Marvin Franz Yap (Animo Repository, 2016)
The study focused on whether the different identity statuses would mediate the relationship between the two forms of parental involvement and the engagement in risk behaviors among Filipino emerging adults. It was also determined whether the two forms of parental involvement would significantly predict the engagement in risk behaviors. Using the scales of Psychological Control Scale Youth Self-Report (Barber, 1996), Child Report of Parent Behavior Inventory (Schaefer, 1965), Extended Version of the Objective Measure of Ego-Identity Status (Bennion & Adams, 1986), and Domain-Specific Risk-Taking Scale for Adult Populations (Blais, & Weber, 2006)., a survey was conducted to 361 Filipino emerging adults whose ages are 18 to 25 years old. Results showed that parental psychological control could lead to an identity foreclosure status which in turn could lead certain levels of engagement in risk behaviors. Parental support could also lead to an identity moratorium status which in turn could lead to certain levels on engagement in risk behaviors. On the other hand, parental psychological control also predicted certain levels of the engagement in risk behaviors. Limitations and further studies were mentioned in this study.